2016
DOI: 10.1210/jc.2015-4101
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Sulfatase Deficiency and Androgen Activation Before and After Puberty

Abstract: Context:Steroid sulfatase (STS) cleaves the sulfate moiety off steroid sulfates, including dehydroepiandrosterone (DHEA) sulfate (DHEAS), the inactive sulfate ester of the adrenal androgen precursor DHEA. Deficient DHEA sulfation, the opposite enzymatic reaction to that catalyzed by STS, results in androgen excess by increased conversion of DHEA to active androgens. STS deficiency (STSD) due to deletions or inactivating mutations in the X-linked STS gene manifests with ichthyosis, but androgen synthesis and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The STS protein is a microsomal enzyme that converts DHEA-S into its unsulfated form of DHEA, which participates in a neurosteroid biosynthesis pathway of the brain5. Current evidence related to how STS genetic variants affect DHEA(S) concentrations is still scarce265253. Relative to previous investigations, the current study is advantaged in providing data about DHEA, DHEA-S and DHEA-S/DHEA ratios specific in ADHD population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The STS protein is a microsomal enzyme that converts DHEA-S into its unsulfated form of DHEA, which participates in a neurosteroid biosynthesis pathway of the brain5. Current evidence related to how STS genetic variants affect DHEA(S) concentrations is still scarce265253. Relative to previous investigations, the current study is advantaged in providing data about DHEA, DHEA-S and DHEA-S/DHEA ratios specific in ADHD population.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the STS gene is correlated with androgen synthesis and metabolism26, while STS deficiency has been proposed as a risk factor for ADHD1927. Chatterjee et al 28.…”
mentioning
confidence: 99%
“…Mutations in the X-localized gene for the steroid STS cause a skin condition known as X-linked ichthyosis (5), due to a build-up of cholesterol sulfate in the stratum corneum of the skin and visible scaling. Androgen metabolism and steroid secretion had been studied recently in a cohort of male X-linked ichthyosis patients before and after puberty (162). Circulating DHEAS was increased in these patients, whereas serum DHEA and testosterone were decreased.…”
Section: Human Genetic Variation and Clinical Outcomesmentioning
confidence: 99%
“…This equilibrium was thought to be maintained by 2 counteracting enzymes, the DHEA sulfotransferase SULT2A1, responsible for sulfate conjugation of the DHEA molecule, and steroid sulfatase, STS, cleaving the sulfate group off the DHEAS molecule to make it accessible for downstream activation towards active androgens. However, in a number of in vivo studies, we have previously shown that the inactivating step catalyzed by SULT2A1 is the predominant direction in normal human physiology, whereas STS activity makes only minor contributions to androgen activation [131-133]. …”
Section: Monogenic Disorders Of Adrenal Steroidogenesismentioning
confidence: 99%